Alternate host plants for Spodoptera frugiperda (LEPIDOPTERA: NOCTUIDAE) in Gunungkidul and Sleman regencies, Yogyakarta, Indonesia - Ichsan Luqmana Indra Putra,; Ika Tensi Dyati,; Wida Afrindini, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Spodoptera frugiperda is a polyphagous insect originating from the Americas and has been found attacking maize in Indonesia. The purpose of this study was to determine the plants that could be alternative hosts for S. frugiperda in Gunungkidul and Sleman Regencies, Yogyakarta, Indonesia. This research was conducted in November 2021 - May 2022. Samples were taken around corn plantations in all sub-districts in Gunungkidul and Sleman Regencies. Two villages were taken from each sub-district using simple random sampling. In each of the village, one corn planting area was selected for a purposive sampling location. The criteria for the host plants taken were plants with attack symptoms from S. frugiperda. The alternative host plant species obtained consisted of 21 plant species in Gunungkidul Regency and 20 plant species in Sleman Regency. The plant families whose members of the species were most frequently attacked by S. frugiperda from the two Regencies were Fabaceae (8 species) and Poaceae (7 species). The conclusion of this study is that S. frugiperda has attacked other crops besides maize in Gunungkidul and Sleman districts, with the most attacked plants were the Fabaceae and Poaceae families.